Custom pyrosequencing assay to detect short BRAF deletions in Langerhans cell histiocytic lesions. Issue 8 (1st September 2020) - Jouenne, Fanélie; Sadoux, Aurélie; Lorillon, Gwenaël; Louveau, Baptiste; Bugnet, Emmanuelle; Meignin, Veronique; Mourah, Samia; Tazi, Abdellatif
Abstract : Langerhans cell histiocytosis (LCH) is a rare inflammatory myeloid neoplastic disease driven by activating mutations in the mitogen-activating protein kinase signalling pathway, including the BRAF V600E mutation and BRAF deletions ( BRAF del). Next-generation sequencing and whole exome sequencing (WES) are valuable and powerful approaches for BRAF del identification, but these techniques are costly and time consuming. Pyrosequencing is an alternative method that has the potential to rapidly and reliably identify gene deletions. We developed a custom pyrosequencing assay to detect the exon-12 BRAF del in 18 biopsies from adult patients with LCH, which were all genotyped in parallel using Sanger sequencing and WES. A BRAF del was detected in 7/18 (39%), 6/18 (33%) and 3/18 (17%) LCH lesions using WES, pyrosequencing and Sanger, respectively, with good concordance between the WES and pyrosequencing results (Kappa-coefficient=0.88). Therefore, our pyrosequencing assay is reliable and useful for detecting BRAF del, particularly in BRAF V600E -negative LCH lesions, for which targeted treatment is indicated.